2020
DOI: 10.1521/bumc_2020_84_02
|View full text |Cite
|
Sign up to set email alerts
|

Altered habenula resting state functional connectivity in deprived veteran tobacco smokers: A pilot study

Abstract: This study aimed to examine habenular resting state functional connectivity (RSFC) abnormalities in tobacco-smoking veterans. The authors explored RSFC in sated smokers (n = 18), overnight deprived smokers (n = 13), and nonsmoker controls (n = 26). Seed-to-voxel analysis was used to explore RSFC in the habenula. Compared to sated smokers, deprived smokers demonstrated higher RSFC between the right habenula and two clusters of voxels: one in the right fusiform gyrus, and one in the left lingual gyrus. To study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…This suggests that nAChR transmission in the mHb-IPn circuit is likely to control nicotine intake in human smokers even after the habit has been established. Indeed, functional brain imaging studies have shown that nicotine modulates habenular activity in both nonsmokers and habitual smokers ( Flannery et al, 2019 ; Jennings et al, 2020 ). Notably, mHb neurons receive excitatory and inhibitory synaptic input almost exclusively from the posterior septum via the stria medullaris (Sperlagh et al, 1998; Qin and Luo, 2009 ; Yamaguchi et al, 2013 ; Otsu et al, 2018 ), with ATP thought to function as a neurotransmitter at the septo-mHb synapse ( Edwards et al, 1992 ; Sperlagh et al, 1995).…”
Section: Nondopamine Mechanisms Of Nicotine Aversionmentioning
confidence: 99%
“…This suggests that nAChR transmission in the mHb-IPn circuit is likely to control nicotine intake in human smokers even after the habit has been established. Indeed, functional brain imaging studies have shown that nicotine modulates habenular activity in both nonsmokers and habitual smokers ( Flannery et al, 2019 ; Jennings et al, 2020 ). Notably, mHb neurons receive excitatory and inhibitory synaptic input almost exclusively from the posterior septum via the stria medullaris (Sperlagh et al, 1998; Qin and Luo, 2009 ; Yamaguchi et al, 2013 ; Otsu et al, 2018 ), with ATP thought to function as a neurotransmitter at the septo-mHb synapse ( Edwards et al, 1992 ; Sperlagh et al, 1995).…”
Section: Nondopamine Mechanisms Of Nicotine Aversionmentioning
confidence: 99%